Co-activation of AMPK and mTORC1 Induces Cytotoxicity in Acute Myeloid Leukemia - Sujobert, Pierre; Poulain, Laury; Paubelle, Etienne; Zylbersztejn, Florence; Grenier, Adrien; Lambert, Mireille; Townsend, Elizabeth C.; Brusq, Jean-Marie; Nicodeme, Edwige; Decrooqc, Justine; Nepstad, Ina; Green, Alexa S.; et al. (Cell reports (Cambridge), 2015)
AMPK is a master regulator of cellular metabolism that exerts either oncogenic or tumor suppressor activity depending on context. Here, we report that the specific AMPK agonist GSK621 selectively kills acute myeloid leukemia (AML) cells but spares normal hematopoietic progenitors. This differential sensitivity results from a unique synthetic lethal interaction involving concurrent activation of AMPK and mTORC1. Strikingly, the lethality of GSK621 in primary AML cells and AML cell lines is abrogated by chemical or genetic ablation of mTORC1 signaling. The same synthetic lethality between AMPK and mTORC1 activation is established in CD34-positive hematopoietic progenitors by constitutive activation of AKT or enhanced in AML cells by deletion of TSC2. Finally, cytotoxicity in AML cells from GSK621 involves the eIF2α/ATF4 signaling pathway that specifically results from mTORC1 activation. AMPK activation may represent a therapeutic opportunity in mTORC1-overactivated cancers. [Display omitted] •AMPK activation blocks AML propagation without toxicity to normal hematopoiesis•Cytotoxicity induced by an AMPK activator (GSK621) involves autophagy in AML•Co-activation of AMPK and mTORC1 is synthetically lethal in AML•AMPK and mTORC1 crosstalk requires eIF2α/ATF4 signaling Sujobert et al. show that specific AMPK activation by GSK621 induces cytotoxicity in AML but not in normal hematopoietic cells. AMPK-mediated cytotoxicity indeed requires mTORC1 activation that is unique to AML cells and involves the eIF2α/ATF4 signaling pathway. This indicates a potential for AMPK-activating agents in the treatment of mTORC1-overactivated cancers.